To pimp a butterfly - Maner, Sequoia (33 1/3, 2022)
"This book dives into the sounds, images, and lyrics of To Pimp a Butterfly to suggest that Kendrick appeals to the psyche of a nation in crisis and embraces the development of a radical political conscience. Kendrick breathes life into the black musical protest tradition and cultivates a platform for loving resistance. Combining funk, jazz, and spoken word, the expansive sonic and lyrical geography brings a level of innovation to a field dominated by the predictability of trap music. More importantly, Kendrick's introspective and philosophical songs compel us to believe in a future where we gon' be alright!"--